Grounding Critique : Marxism, Concept Formation, and Embodied Social Relations - Tanyildiz, Gökbörü Sarp, (Social Sciences E-Books Online, Collection 2025., 2025)
Grounding Critique: Marxism, Concept Formation, and Embodied Social Relations argues that marxism must have a robust understanding of embodied social relations, such as race, gender, and sexuality, in order to produce the knowledge necessary for transformative social change. Tanyildiz subjects two important strands of marxist social theory -marxist-feminism and social reproduction theory- to a methodological examination and demonstrates their shortcomings. Focusing on these strands' critiques of intersectionality as a moment of crystallization in concept formation, Grounding Critique explores alternative ways of using Marx's method to understand contemporary human praxis. See Less